D-DIMER AS A PROGNOSIS OF THE SEVERITY OF COVID-19 PATIENTS AT BEKASI REGENCY HOSPITAL - Kurniawati, Dyah Eka (Universitas Airlangga, 2024)
The increase in D-dimer is the most significant change in coagulation parameters in Covid-19 patients and can be a marker of poor prognosis. The purpose of this study was to see the average significant D-dimer levels in patients with confirmed Covid-19 with severity. The method used is Retrospective Research with a purposive sampling technique based on the criteria of the severity of Covid-19 disease. Patient data was taken from medical records and D-dimer levels from the Laboratory Information System and then analyzed using a one-way Anova test. The results showed an average D-dimer level of 2.66 mg/L at critical degrees, 2.02 mg/L at severe degrees, 0.30 at moderate degrees and 0.26 at mild degrees. Male patients occupy a larger percentage than female patients with a total of 62.5%. The age of 46-65 years occupies the highest percentage of 55% for the abnormal category because the immune system as a protector of the body does not work as strongly as when it was young. This study showed a significant average difference in the groups of mild severity with severe, mild with critical, moderate with severe, and moderate with critical. For the next researcher, it is expected to be able to analyze other hemostasis examination parameters with variables of disease severity. Kata kunci: Coronavirus, COVID-19, D-dimer, parameter koagulasi, pembekuan darah